Protein-Ligand Interactions Methods and Applications - Williams, Mark A.; Daviter, Tina.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2013)
Proteins are the cell’s workers, their messengers and overseers. In these roles, proteins specifically bind small molecules, nucleic acid and other protein partners. Cellular systems are closely regulated and biologically significant changes in populations of particular protein complexes correspond to very small variations of their thermodynamics or kinetics of reaction. Interfering with the interactions of proteins is the dominant strategy in the development of new pharmaceuticals. Protein Ligand Interactions: Methods and Applications, Second Edition provides a complete introduction to common and emerging procedures for characterizing the interactions of individual proteins. From the initial discovery of natural substrates or potential drug leads, to the detailed quantitative understanding of the mechanism of interaction, all stages of the research process are covered with a focus on those techniques that are, or are anticipated to become, widely accessible and performable with mainstream commercial instrumentation. Written in the highly successful Methods in Molecular Biology series format, chapters contain introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and notes on troubleshooting and avoiding known pitfalls. Authoritative and accessible, Protein Ligand Interactions: Methods and Applications, Second Edition serves as an ideal guide for researchers new to the field of biophysical characterization of protein interactions – whether they are beginning graduate students or experts in allied areas of molecular cell biology, microbiology, pharmacology, medicinal chemistry or structural biology.
Protein-Ligand Interactions: Fundamentals -- Protein Sample Characterization -- Measurement of Protein-Ligand Complex Formation -- Isothermal Titration Calorimetry for Studying Protein-Ligand Interactions -- Rapid Mixing Kinetic Techniques -- Protein-Ligand Interactions Using SPR Systems -- Fluorescence Techniques in Analysis of Protein-Ligand Interactions -- Circular and Linear Dichroism Spectroscopy for the Study of Protein-Ligand Interactions -- Analyzing Protein-Ligand Interactions by Dynamic NMR Spectroscopy -- Studying Metal Ion - Protein Interactions: Electronic Absorption, Circular Dichroism and Electron Paramagnetic Resonance -- Monitoring Protein-Ligand Interactions by Time-resolved FTIR Difference Spectroscopy -- Biophysical Methods in Drug Discovery from Small Molecule to Pharmaceutical -- Biophysical Screening for the Discovery of Small-Molecule Ligands -- Screening Protein-Small Molecule Interactions by NMR -- Model Membrane Systems -- Quantitative Fluorescence Co-localization to Study Protein-Receptor Complexes -- Studying Protein-Ligand Interactions Using X-Ray Crystallography -- Molecular Fields in Ligand Discovery -- Structure-Based Virtual Screening for Novel Ligands.
Keywords: Proteins .; Protein Science; Protein-Ligand Interactions